Heart rate reserve versus talk test : is there a similar training effect? - Suckow, Samantha (My University, 2016)
This study was designed to determine if there were similar increases in maximal oxygen consumption (V02max) when training using the traditional Heart Rate Reserve (1-IRR) method of gauging exercise intensity versus the Talk Test (TT) method of gauging exercise intensity. Forty-four healthy, previously inactive, subjects were randomized into two training groups: TT group (n=20) and HRR group (n=24). Performance variables assessed included absolute and relative V02max, absolute and relative peak power output (PPO), and maximal heart rate (1-IRmax). It was found that in both groups, there was a significant increase in absolute V02max, relative V02max, and absolute PPO after 10 weeks of training. The only significant difference between groups was the increase in absolute PPO (watts). The TT group increased by 34 watts, while the HRR group increased by only 24 watts. The results of this study suggest prescribing exercise using the TT, which is a simpler method of gauging exercise intensity, may be just as good as the traditional %HRR guidelines for improving aerobic capacity.
Keywords: Heart function tests; Exercise--physiological aspects; Kinesiology